A case of diabetic ketoacidosis with hemorrhagic gastric ulcer. (24th May 2021) - Isono, Momoko; Isono, Hiroki; Ihara, Kousuke; Oogi, Maki
Abstract : This is a case of diabetic ketoacidosis with hemorrhagic gastric ulcer. Mortality rates increase when DKA is complicated with upper gastrointestinal bleeding, so it is important to consider this possibility.